Analisis Kinerja Lalu Lintas Pada Ruas Jalan Jendral Sudirman Kabupaten Kuningan - Salsabila, Alfida; Hariani, Mira Lestira (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2024)
The traffic performance analysis research on this road section was carried out on Jalan Jendral Sudirman Kuningan Regency. The road has a high density. In connection with this, research is needed using the 1997 Indonesian Road Capacity Manual (MKJI) method. This research aims to analyze the performance of the Jendral Sudirman road section and provide technical recommendations that can be applied to the Jendral Sudirman road section. After conducting research at the observation location, the capacity value for peak hour is 2245.47 smp / hour, the degree of saturation is 0.70 (crowded smoothly), and the level of road service is included in the